Ectopic integration vectors for generating fluorescent promoter fusions in bacillus subtilis with minimal dark noise - Trauth, Stephanie; Bischofs-Pfeifer, Ilka (PLOS ONE, 2014)
Fluorescent protein promoter reporters are important tools that are widely used for diverse purposes in microbiology, systems biology and synthetic biology and considerable engineering efforts are still geared at improving the sensitivity of the reporter systems. Here we focus on dark noise, i.e. the signal that is generated by the empty vector control. We quantitatively characterize the dark noise of a few common bacterial reporter systems by single cell microscopy. All benchmarked reporter systems generated significant amounts of dark noise that exceed the cellular autofluorescence to different extents. We then reengineered a multicolor set of fluorescent ectopic integration vectors for Bacillus subtilis by introducing a terminator immediately upstream of the promoter insertion site, resulting in an up to 2.7-fold reduction of noise levels. The sensitivity and dynamic range of the new high-performance pXFP_Star reporter system is only limited by cellular autofluorescence. Moreover, based on studies of the rapE promoter of B. subtilis we show that the new pXFP_Star reporter system reliably reports on the weak activity of the rapE promoter whereas the original reporter system fails because of transcriptional interference. Since the pXFP_Star reporter system properly isolates the promoter from spurious transcripts, it is a particularly suitable tool for quantitative characterization of weak promoters in B. subtilis.